Adjunctive Benefit of High-Field 3 Tesla MRI Guidance in Endoscopic Transsphenoidal Resection of Pituitary Adenoma - Kartik Manoj Multani; Anandh Balasubramaniam; Boyina Jagadeshwar Rajesh; Krishna Kumar; Nitin Manohar; Anjani Kumar (Indian Journal of Neurosurgery)
Introduction Pituitary adenomas (PAs) although benign, are difficult to resect intracranial tumors and their residues are associated with morbidity and reduced quality of life. Thus, gross total resection (GTR) is the goal for all PAs. Role of various modalities for better intraoperative visualization and thus improve resection of adenoma have been tested and each have their pros and cons. The aim of this paper is to analyze adjunctive benefit of high-field 3 Tesla intraoperative magnetic resonance imaging (iMRI) in PAs resection by endoscopic transnasal transsphenoidal surgery (eTSS). Materials and Methods A total of 50 patients who underwent iMRI-guided eTSS were included. MRI findings in preoperative, intraoperative, and 3 months postoperative stage were compared. Adjunctive value of iMRI in improving resection rates of adenoma, postoperative endocrinological outcomes, need for adjuvant radiotherapy, and postoperative cerebrospinal fluid leak rates was assessed. Results High-field 3 Tesla iMRI helped us to detect residues in 24 (48%) patients and iMRI-guided second look surgery increased our GTR rates from initial 52 to 80% and also helped us to identify and achieve 100% GTR in intrasellar residues and parasellar residues that were medial to medial carotid tangential line. With better resection rates, need for adjuvant radiotherapy was also reduced and only 2% received adjuvant radiotherapy. Average increase in surgical time with the use of iMRI was 38.78 minutes without any side effects pertaining to prolonged surgery. Conclusion High-field iMRI is a useful adjunct in assessment and improvement in extent of resection of PA by endoscopic transsphenoidal surgery. Also, it was found beneficial in preserving normal anatomical gland and, thus, reducing the need for postoperative adjuvant hormonal and radiation therapy.